The revenge: Kerachut / Isma Noornisa Ismail and Nur Ilianis Adnan - Ismail, Isma Noornisa; Adnan, Nur Ilianis (Academy of Language Studies, 2023)
Lisa and Fiza attended the same high school, and they were very close to one another. Or so Lisa thought. They were almost inseparable and they always did everything together. Little does Lisa realise that Fiza has been harbouring rage and jealousy within her. She felt that Lisa always gets whatever she wants easily, and it's the last straw when Lisa confessed that she has a crush on Adi - the only guy that Fiza has set her heart on. That evening, their class teacher announced about an upcoming trip to Pantai Kerachut, a beautiful, secluded beach in Penang and asked if the students would like to join. Both girls excitedly listed their names as they saw that Adi is also going. "The time has come for Lisa to know her true place. She can't go on living happily while I'm miserable. Adi is mine!" thought Fiza, scheming in her head. They happily prepared for the trip, buying new matching swimsuits, beach hats and other necessities. After a couple of weeks, the day for their trip finally arrived. Lisa and Fiza arrived early at school, excited with the prospect of spending more relaxing time with Adi, their subject of obsession. Soon, the teacher called out all the names in her list to board the bus. One by one, all the students had been called, including Adi and Fiza, which only left Lisa standing alone by the bus. Then, the teacher noticed her and asked, "what are you doing here Lisa? I thought you had cancelled your name. Are you here to send Fiza off? How sweet of you. '' Lisa felt silly standing there in her beachwear as her friends waved goodbye and the bus took off. She wanted to cry but no tears came as she was too humiliated with the whole incident. She had been bragging to everyone about going on the trip and having fun with Adi only to be left all alone by the curb. "Ting!" a notification from her phone surprised her. She took it out and checked out the latest Insta Story by Fiza who shot a video of her having a whale of time with the person sitting next to her in the bus, Adi.